Insights in Public Health: The Hawai‘i Home Visiting Network: Evidence-Based Home Visiting Services in Hawai‘i - Yoshimoto, D Kaulana (University Clinical, Education & Research Associate (UCERA), 2014)
Home visiting services are cost-effective and improve the health of children and families among those at increased risk. From 1985–2008, home visiting services in Hawai‘i were provided primarily through state funding of the Hawai‘i Healthy Start Program, but the program was severely reduced due to the economy and state budget changes over the past decade. The Maternal and Child Health Branch (MCHB) in the Family Health Services Division responded to these changes by seeking out competitive grant opportunities and collaborations in order to continue to promote home visiting services to those children and families in need. In 2010, the MCHB was awarded a federally funded Maternal, Infant and Early Childhood Home Visiting (MIECHV) grant for home visiting services to promote maternal, infant, and early childhood health, safety and development, strong parent-child relationships, and responsible parenting. In 2011, the MCHB was also awarded a competitive MIECHV development grant that funded the re-establishment of the hospital Early Identification program. Families in need of additional support identified through this program are referred for family strengthening services to a network of existing home visiting programs called the Hawai‘i Home Visiting Network (HHVN). The HHVN is supported by MIECHV and a small amount of state funds to assist programs with capacity building, training, professional development, quality assurance, and accreditation/certification support. The MIECHV grant requires that programs are evidence-based and address specific outcome measures and benchmarks. The HHVN provides home visiting services to families prenatally through 5 years of age that reside in specific at-risk communities, and is aimed at fostering positive parenting and reducing child maltreatment using a strength-based approach by targeting six protective factors: (1) social connections, (2) nurturing and attachment, (3) knowledge of parenting and child development, (4) parental resilience, (5) social and emotional competence of children, and (6) concrete supports for parents. This article provides an introduction to the HHVN as a diverse network of evidence-based home visiting programs with services currently available on all islands, and highlights aspects of home visiting programs that support the Family-Centered Medical Home (FCMH) model. The HHVN provides important services to families at risk and uses evidence-based practices to yield positive results. Health care professionals can support this network to promote the health of children and families by being aware that these home visiting services exist and encouraging families at-risk to participate. Continued collaboration and expanded partnerships with health providers can help strengthen the home visiting network and improve outcomes for children and families in Hawai‘i.